Design-Thinking Mindsets Facilitating Students’ Learning of Scientific Concepts in Design-Based Activities: Research Article - Ladachart, Luecha; Radchanet, Visit; Phothong, Wilawan (Journal of Turkish Science Education, 2022)
Design-based learning has been internationally recognized as a key approach to science, technology, engineering, and mathematics (STEM) education at K-12 levels, where students are encouraged to learn STEM through the engineering design process. In this regard, it is argued that design-thinking mindsets play a crucial role in facilitating students’ learning of STEM when engaging in design-based activities. While research has indicated that design-based learning can facilitate students’ learning of scientific concepts, it is unclear whether, and which dimensions of, design-thinking mindsets support the conceptual learning of science. This study aims to explore 37 eighth-grade students’ conceptual learning and design-thinking mindsets in the context of design-based learning on pulleys. The students completed two instruments, namely a conceptual test on pulleys and a Likert-scale questionnaire measuring design-thinking mindsets, before and after the design-based learning. In a comparison between two classes of students, using the non-parametric method of Mann-Whitney U tests in each measurement, some dimensions of design-thinking mindsets that facilitate conceptual learning on pulleys were identified. These dimensions included: (a) mindfulness to the process and impacts on others; and (b) orientation to learning by making and testing. Based on these results, recommendations for the effective enactment of design-based learning in order to develop students’ scientific understanding are provided.
Keywords: Conceptual learning; Design-based learning; Design thinking; Pulleys; STEM Education